Do means-tested benefits reduce the demand for annuities? - Evidence from Switzerland - Monika Bütler; Stefan Staubli; Kim Peijnenburg (Verein für Socialpolitik, 2010)
Most industrialized countries provide a subsistence level consumption floor in old age, usually in the form of means-tested benefits or income supplements. The availability of such means-tested payments creates an incentive to optimally cash out (occupational) pension wealth for low and middle income earners. In case the guaranteed old-age income exceeds first-pillar benefits, individuals with low wealth find it unambiguously optimal to cash out, because the annuity income from pension wealth reduces the means tested benefits one for one. Agents with intermediate wealth levels weigh the advantages from annuitization, namely the longevity risk insurance and a smooth consumption pattern, against the disadvantage, which is giving up free wealth in the form of means-tested benefits. We analyze optimal annuity demand and consumption/savings decisions in a realistic life-cycle model under a social security scheme in which means-tested benefits can be claimed if income falls below a certain subsistence level. The model is calibrated to Switzerland, which is an interesting case because it combines generous means-tested benefits with a large second pillar in which accumulated pension wealth can be cashed out at retirement. We show that the predicted annuitization rates are roughly consistent with the cash-out patterns observed in Switzerland. Means-tested benefits can reduce the annuitization levels substantially, which can generate both non-negligible welfare losses and high government expenditures.
Keywords: D91; G23; J26; 330; Means-Tested Benefits; Occupational Pension; Annuity